Efektivitas Audit Kepatuhan Belanja Bantuan Sosial APBN Kementerian Sosial Tahun 2020-2023 - Hamdani, Hamdani (Universitas Batanghari Jambi, 2025)
This research aims to ensure that compliance audits align with audit objectives, with entities following up on social assistance management audits and improvements, targeting the assurance that social assistance policies and management comply with established regulations. The research results indicate that the implementation of the compliance audit has met the audit objectives. Meanwhile, the effectiveness of the audit from the follow-up aspect shows a lack of compliance by the Ministry of Social Affairs in following up. The comparison of recommendations with follow-up actions shows that in the 2019 social assistance audit, there were 20 recommendations and 10 were followed up, in 2020 there were 37 recommendations and 21 were followed up, in 2021 there were 38 recommendations and 27 were followed up, and in 2022 there were 32 recommendations and 21 were followed up. Furthermore, the effectiveness of the social assistance audit is marked by recurring audit findings from previous years, namely in 2020, out of 10 findings, 2 were from 2019; in 2021, out of 13 findings, 3 were from 2020; in 2022, out of 9 findings, 3 were from 2021; and in 2023, out of 11 findings, 7 were from 2022.